Electrochemical Reduction of Oxygen in Aprotic Ionic Liquids Containing Metal Cations: A Case Study on the Na–O2 system. Issue 7 (14th March 2017) - Azaceta, Eneko; Lutz, Lukas; Grimaud, Alexis; Vicent‐Luna, Jose Manuel; Hamad, Said; Yate, Luis; Cabañero, German; Grande, Hans‐Jurgen; Anta, Juan A.; Tarascon, Jean‐Marie; Tena‐Zaera, Ramon
Abstract: Metal–air batteries are intensively studied because of their high theoretical energy‐storage capability. However, the fundamental science of electrodes, electrolytes, and reaction products still needs to be better understood. In this work, the ionic liquid N ‐butyl‐ N ‐methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR14TFSI) was chosen to study the influence of a wide range of metal cations (M n + ) on the electrochemical behavior of oxygen. The relevance of the theory of Lewis hard and soft acids and bases to predict satisfactorily the reduction potential of oxygen in electrolytes containing metal cations is demonstrated. Systems with soft and intermediate M n + acidity are shown to facilitate oxygen reduction and metal oxide formation, whereas oxygen reduction is hampered by hard acid cations such as sodium and lithium. Furthermore, DFT calculations on the energy of formation of the resulting metal oxides rationalize the effect of M n + on oxygen reduction. A case study on the Na–O2 system is described in detail. Among other things, the Na + concentration of the electrolyte is shown to control the electrochemical pathway (solution precipitation vs. surface deposition) by which the discharge product grows. All in all, fundamental insights for the design of advanced electrolytes for metal–air batteries, and Na–air batteries in particular, are provided. Abstract : The softer the better : The oxygen reduction reaction (ORR) in an aprotic ionic liquid is found to be governed by the Lewis acidity of metal cations. Soft cations catalyze the ORR at less negative onset potentials, whereas hard cations hamper the ORR and result in more negative onset potentials. These findings are relevant to designing advanced electrolytes for high‐performance metal–air batteries.